Theory and applications of InfraRed and thermal image analysis in ergonomics research - Luximon, Ameersing; Chao, Huang; Goonetilleke, Ravindra S.; Luximon, Yan (Frontiers in Computer Science, 2022)
Designing products and services to fit human needs, wants and lifestyle require meaningful data. With Industry 4.0 and the internet of things, we have many ways to capture data using sensors and other means. Infrared (IR) cameras are quite ubiquitous, especially for screening illness and wellness. They can provide a wealth of data on different objects and even people. However, their use has been limited due to processing complexities. With reducing cost and increasing accuracy of IR cameras, access to thermal data is becoming quite widespread, especially in medicine and people-related applications. These cameras have software to help process the data, with a focus on qualitative analyses and rather primitive quantitative analyses. In ergonomics, data from multiple users are essential to make reasonable predictions for a given population. With four experiments, we show how IR images and videos, can be made useful for human-centered design. More research is needed for modeling IR data in other applications.